2022
DOI: 10.3389/fcvm.2022.966126
|View full text |Cite
|
Sign up to set email alerts
|

Valve-sparing David procedure via minimally invasive access does not compromise outcome

Abstract: ObjectivesAortic valve sparing-aortic root replacement (David procedure) has not been routinely performed via minimally invasive access due to its complexity. We compared our results of elective David procedure via minimally invasive access to those via a full sternotomy.MethodsBetween 1993 and 2019, a total of 732 patients underwent a valve sparing root replacement (David) procedure. Out of these, 220 patients underwent elective David-I procedure (isolated) without any other concomitant procedures at our cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“… Schematic representation and summary of the currently available access techniques. Yellow dotted lines represent the respective incisions [ 6 , 7 , 9 , 10 , 11 , 13 , 14 , 17 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… Schematic representation and summary of the currently available access techniques. Yellow dotted lines represent the respective incisions [ 6 , 7 , 9 , 10 , 11 , 13 , 14 , 17 ]. …”
Section: Figurementioning
confidence: 99%
“…Over the last decade, the minimally invasive access has more and more become the standard approach for coronary revascularization and mitral valve surgery as well as for aortic valve and aortic root replacement [ 2 , 3 , 4 , 5 ]. Here, Shrestha et al reported comparable peri- and postoperative outcomes in 42 patients undergoing David procedure through an upper hemisternotomy compared to 178 patients operated through full sternotomy, while operation and cross clamp times were slightly longer [ 6 ]. As the next logical step, minimally invasive approaches for more complex operations including the supracommissural ascending aorta have currently moved into the center of attention.…”
Section: Introductionmentioning
confidence: 99%
“…Additional procedures were performed whenever indicated and included coronary bypasssurgery, additional valve-surgery or (partial) replacement of the aortic arch. Despite technically possible through minimally invasive access (7), for the sake of optimal exposure and considering the potential need for concomitant procedures, all David operations in this study were performed through a full sternotomy.…”
Section: Operative Techniquementioning
confidence: 99%
“…Therefore, minimally invasive David procedure via an upper ministernotomy is an excellent example of MICS. Nevertheless, AV repair and VSARR are complex and demanding procedures and therefore still not routinely performed in MICS, yet technically feasible and safe ( 5 ).…”
Section: Commentmentioning
confidence: 99%